1981
DOI: 10.1111/j.1600-0714.1981.tb01293.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the origin and nature of ‘amyloid’ in a calcifying epithelial odontogenic tumour

Abstract: Fresh and fixed tissue from a resection specimen of a calcifying epithelial odontogenie lumour (CEOT) was prepared for histologieal, histoehemieal, immunological and bioehemical investigation in order to sludy the nature of the amyloid-like material. The fixed tissue gave positive reactions with Congo-red. Thioflavin T and the dimethylamino benzene (DMAB)-method for tryptophan. The diazotization-eoiipling (DC) method for tyrosine was negative. The major protein purified liom Ihe unfixed tissue by sec]ucntial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Ultrastructutally, the fine filaments seen in this tumour are similar in thickness and electron density to amyloid material described elsewhere (Shirahama & Cohen 1967, Tandler 1981. This, together with the positive reaction to both Congo red and thioflavine T, suggests that the fine filaments seen in calcifying epithelial odontogenic tumours are probably a form of amyloid, as has previously been suggested (Ranlov & Pindborg 1966, Gardner et al 1968, Vickers et al 1965, Franklin et al 1981.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Ultrastructutally, the fine filaments seen in this tumour are similar in thickness and electron density to amyloid material described elsewhere (Shirahama & Cohen 1967, Tandler 1981. This, together with the positive reaction to both Congo red and thioflavine T, suggests that the fine filaments seen in calcifying epithelial odontogenic tumours are probably a form of amyloid, as has previously been suggested (Ranlov & Pindborg 1966, Gardner et al 1968, Vickers et al 1965, Franklin et al 1981.…”
Section: Discussionsupporting
confidence: 84%
“…Eosinophilic deposits that display the tinetorial characteristics of amyloid in the calcifying epithelial odontogenic tumour (CEOT) have been subjected to numerous investigations at the light and electron-microscopical level with inconclusive results (Vickers et al 1965, Ranlov & Pindborg 1966, Gardner et al 1968, Anderson et al 1969, Chaudhry et al 1972, Solomon et al 1975, Page et al 1975. The most recent study by Franklin et al (1981), using histological, histochemical, immunologieal and biochemical methods, confirmed that the material gave positive reactions with Congo red, thioflavine T, and was positive for tryptophan and negative for tyrosine. A major protein of molecular weight 9,800 was purified from the tumour and amino-acid analysis showed similarities to tuft-enamel protein, immune amyloid, and the variable light-chain component.…”
mentioning
confidence: 99%
“…Many studies have previously reported this staining characteristic of the amyloid-like material in CEOTs (Franklin et al 1981;El-Labban et al 1983;Asano et al 1990;Takata et al 1993;Aviel-Ronen et al 2000;Germanier et al 2005;Patino et al 2005). Despite the consistency of the positive Congo red reaction, the nature of the amyloid-like substance in CEOT is one of the most controversial topics.…”
Section: Discussionmentioning
confidence: 86%
“…Enzyme histochemical studies have revealed strong alkaline phosphatase activity in the tumor cells (7)(8)(9). The homogenous acellular materials have been variably described as either amyloid-like (10)(11)(12)(13)(14)(15)(16)(17)(18) or not amyloid (5)(6)(7)(19)(20)(21). Electron microscopic studies have detected fibrillar structures in the acellular material that differs from amyloid (22,7,20) and resemble epithelial fibrillar proteins such as keratin (19).…”
mentioning
confidence: 99%